1990
DOI: 10.1002/cne.902930409
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of palatal and laryngeal taste buds in the hamster

Abstract: Mammalian taste buds are distributed within several distinct subpopulations, innervated by branches of three cranial nerves. These taste bud populations originate and mature at different times in various mammalian species and are thought to play differential roles in the control of taste-mediated behaviors. The hamster is a common animal for the electrophysiological study of the gustatory system, and it has been shown that taste buds innervated by the IXth nerve develop postnatally in this species. To delineat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Perhaps the key to the uniqueness of fiber IR in the fungiform bud field relates to the precocious development of fungiform buds in hamster. At birth, the adult complement of fungiform bud pores is already present (Whitehead and Kachele, 1994), in contrast to the postnatal development and maturation of foliate, circumvallate, palatal, and laryngeal buds (Miller and Smith, 1984;Belecky and Smith, 1990). The prominence of subgemmal TrkC-like fibers in mature hamster could reflect their possible earlier role in establishment of precocious fungiform buds or papillae.…”
Section: The Uniqueness Of the Fungiform Gemmal Fieldmentioning
confidence: 91%
“…Perhaps the key to the uniqueness of fiber IR in the fungiform bud field relates to the precocious development of fungiform buds in hamster. At birth, the adult complement of fungiform bud pores is already present (Whitehead and Kachele, 1994), in contrast to the postnatal development and maturation of foliate, circumvallate, palatal, and laryngeal buds (Miller and Smith, 1984;Belecky and Smith, 1990). The prominence of subgemmal TrkC-like fibers in mature hamster could reflect their possible earlier role in establishment of precocious fungiform buds or papillae.…”
Section: The Uniqueness Of the Fungiform Gemmal Fieldmentioning
confidence: 91%
“…The prenatal development of the palatal taste buds was traced in mammalian species such as humans, monkeys, sheep, and cats as well as hamsters (Bradley and Stern, 1967;Bradley et al, 1979;Stedman et al, 1983;Zahm and Munger, 1983;Belecky and Smith, 1990). The present study revealed that the development of rat taste buds is almost prenatal in the SP, whereas most entirely postnatal in the NIP.…”
Section: Temporal and Spatial Development Of The Palatal Taste Budsmentioning
confidence: 99%
“…Taste plays an important role in the regulation of food intake, eliciting the basic response components of ingestion and aversion [Grill and Norgren, 1978;Belecky and Smith, 1990]. The taste buds of rats are distributed not only in the tongue but also in the pharynx, larynx and other regions of the oral cavity [Travers and Nicklas, 1990].…”
Section: Introductionmentioning
confidence: 99%